Promoting 2D Material Photodetectors by Optical Antennas beyond Noble Metals - Yi, Huaxin; Ma, Yuhang; Ye, Qiaojue; Lu, Jianting; Wang, Wan; Zheng, Zhaoqiang; Ma, Churong; Yao, Jiandong; Yang, Guowei (Advanced Sensor Research, 2023)
The distinctive layered crystal structures and diverse properties of 2D layered materials (2DLMs) have established them as prospective building blocks for implementing next‐generation optoelectronics. One critical predicament in terms of light sensing is the weak absorption caused by the atomic‐scale thickness, as well as the limited effective wavelength range/low spectral selectivity constrained by the intrinsic band structures. Despite the fact that numerous noble metal antennas are harnessed for enhancing the light–matter coupling, they suffer from exorbitant cost and narrow resonant optical windows. To this end, a number of non‐noble plasmonic optical antennas have been developed to improve the light‐sensing properties of 2DLM photodetectors, and tremendous advances have been accomplished. Herein, a comprehensive overview of this subject is provided based on four aspects; namely, non‐noble metal antenna promoted 2DLM photodetectors, heteroatom doped semiconductor antenna promoted 2DLM photodetectors, non‐stoichiometric semiconductor antenna promoted 2DLM photodetectors, and MXene antenna promoted 2DLM photodetectors. The focus is on the device structures, preparation, and underlying mechanisms. In the end, the challenges are highlighted, and potential strategies addressing them are proposed, which aim to navigate the upcoming exploration in the related domains and fully exert the pivotal role of non‐noble plasmonic optical antennas toward advancing 2DLM photodetectors. This review delivers a comprehensive picture on improving the light‐sensing properties of 2D layered material photodetectors by exploiting various non‐noble plasmonic optical antennas including non‐noble metals, heteroatom doped semiconductors, non‐stoichiometric semiconductors, and MXenes. In the end, future potential directions are proposed, aiming to provide navigation for the upcoming research efforts in this burgeoning field.